2017
DOI: 10.1007/s13193-017-0651-4
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Role of CEA and MSI Status in Predicting Outcome of CRC Patients: a Perspective Study Amongst Hospital Attending Eastern Indian Populations

Abstract: Carcinoembryonic antigen (CEA) is an important deterministic factor in predicting colorectal carcinoma (CRC) progression. It is also evident that microsatellite instability (MSI) which results in a hypermutable phenotype of genomic DNA is common in CRC. Owing to the scarcity of reports from India, our aim of this study was to understand the clinicopathological correlations of CEA status with surgery and chemotherapy, correlate the same with socio-demographic status of the patients, determine the MSI status amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…In our cohort, KRAS-mutated tumors were more frequently found in the MSS group, which is consistent with the findings of previous studies 29 , 39 . A previous study by Koyel et al reported a strong association between high CEA (≥ 4) and MSI-H, which is also reflected in the present study 40 .…”
Section: Discussionsupporting
confidence: 90%
“…In our cohort, KRAS-mutated tumors were more frequently found in the MSS group, which is consistent with the findings of previous studies 29 , 39 . A previous study by Koyel et al reported a strong association between high CEA (≥ 4) and MSI-H, which is also reflected in the present study 40 .…”
Section: Discussionsupporting
confidence: 90%
“…In our cohort, KRAS-mutated tumors were more frequently found in the MSS group, which is consistent with the findings of previous studies [24,33]. A previous study by Koyel et al reported a strong association between high CEA (≥4) and MSI-H, which is also reflected in the present study [34].…”
Section: Discussionsupporting
confidence: 93%
“…Compared to other potential predictive markers, measurement of serum CEA levels is inexpensive, standardized, widely used and easily performed [18]. In recent years, many studies have focused on the predictive value of CEA levels in patients with colorectal cancer receiving chemotherapy or chemoradiotherapy [19][20][21]. Most studies showed that low pre-treatment CEA levels are associated with a good patients' outcome [21], but only very few data are available on the predictive role of CEA measurements in CRLM patients undergoing curatively intended liver surgery, supporting further analyses addressing this question in large and well-characterized cohorts of patients [22,23].…”
Section: Discussionmentioning
confidence: 99%